Rekindled Russia-African Relations and Implication on UN Peacekeeping Efforts in the DRC (Global Journal of Human-Social Science, 2025)
The paper is devoted to analysing the impact of rekindled relations between the Russian Federation and its African friends The Russian Federation has in recent years intensified its interactions with several African countries The cooperation is rooted in the Soviet era when the USSR aided most African countries to gain independence The paper notes that today Russia s partnership with African countries is becoming increasingly intensive and multifaceted on the economic political military and even social fronts The relations are grounded in the theory of mutualism coined by Proudhon in the mid-19th century This paper also discussed how rekindled military relations may aid in the pacification of numerous conflicts bedeviling the continent As a case study the paper looked at how Russia can help the United Nations in its peacekeeping efforts in the Democratic Republic of Congo by taking advantage of the economic cooperation and military relations between the two countries In this regard the paper found that economic cooperation based on mutually beneficial and symbiotic relations could help improve the ailing Congolese economy Furthermore the provision of military training and modern weapons by Russia may capacitate the Congolese military to deal with the numerous rebels in that country effectively As a Permanent member of the United Nations Security Council Russia should help stop the looting of Congolese resources The paper used qualitative methods to exploit a large pool of Russian policy documents and scholarly works on Russia Africa relations and also conducted interviews with both Russian and African policy makers The paper recommends that the DRC should abandon old and unbeneficial relations with former colonial masters and embrace Russia whose policy is predicated on mutually beneficial relations